1999
DOI: 10.1001/archpsyc.56.7.639
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mechanisms Underlying Impaired Recognition Memory and Conscious Awareness in Patients With Schizophrenia

Abstract: Patients with schizophrenia are unable to link the separate aspects of events into a cohesive, memorable, and distinctive whole. The corollary of this defective relational binding is a quantitative and qualitative impairment of autonoetic awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
150
2
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(181 citation statements)
references
References 33 publications
20
150
2
8
Order By: Relevance
“…Interestingly, levels of cued recall were lower than stem completion throughout, but lowest in the high-dose ketamine group where twice as many stems were completed with targets in the implicit compared to the explicit task. This would accord with the suggestion that in situations where conscious awareness is impaired, it may serve to have inhibitory effects on explicit memory (Danion et al 1999). Preserved perceptual priming is of interest as no previous study has examined the effects of ketamine on this form of memory.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, levels of cued recall were lower than stem completion throughout, but lowest in the high-dose ketamine group where twice as many stems were completed with targets in the implicit compared to the explicit task. This would accord with the suggestion that in situations where conscious awareness is impaired, it may serve to have inhibitory effects on explicit memory (Danion et al 1999). Preserved perceptual priming is of interest as no previous study has examined the effects of ketamine on this form of memory.…”
Section: Discussionsupporting
confidence: 71%
“…Evidence for a problem of this type in memory tasks has recently been reported in a series of studies by Danion and his colleagues (e.g. Danion et al 1999 ;Bacon et al 2001). These authors conclude that the memory problems shown by patients with schizophrenia lie in the domain of meta-memory and reflect an impaired conscious awareness of one's own knowledge.…”
Section: A Disorder Of Consciousness ?mentioning
confidence: 92%
“…determining if information was self-generated or provided by the experimenter) (Bentall et al, 1991;Rankin and O'Carroll, 1995). Such findings raise the possibility that episodic memory deficits in patients with schizophrenia may be related to a failure of binding features together to create more complex representations (Rizzo et al, 1996;Danion et al, 1999). Most studies, however, do not separately assess memory for individual features and memory for bound features.…”
Section: Introductionmentioning
confidence: 99%